Survey dataset on open and distance learning students’ intention to use social media and emerging technologies for online facilitation - Arulogun, Oladiran Tayo; Akande, Oluwatobi Noah; Akindele, Akinyinka Tosin; Badmus, Taofeeq Alabi (Data in brief, 2020)
Open and Distance Learning (ODL) students rely majorly on the use of Information, Communication and Technology (ICT) tools for online facilitation and other activities supporting learning. With emphasis on ODL students of Ladoke Akintola University of Technology (LAUTECH), Oyo Sta te, Nigeria; Moodle Learning Management System (LMS) has being the major medium for online facilitation for the past 5 years. Therefore, this data article presents a survey dataset that was administered to LAUTECH ODL students with a view to assess their readiness to accept and use alternative social media platforms and emerging technologies for online facilitation. The data article also includes questionnaire instrument administered via google form, 900 responses received in spreadsheet formats, chats generated from the responses, the Statistical Package of the Social Sciences (SPSS) file, the descriptive and reliability statistics for all the variables. Authors believe that the dataset will guide policy makers on the choice of social media and emerging technologies to be adopted as a facilitation tool for ODL students. It will also reveal the challenges that could militate against the willingness to use these supplementary modes of learning from students’ perspectives.